Kajian Kriminologis Terhadap Tindak Pidana Pencabulan Anak Yang Disertai Kekerasan - Sherly Pattianakota; Sherly Adam; Yanti Amelia Lewerissa (Faculty of Law Universitas Pattimura, 2023)
Crimes involving child molestation are categorized as criminal acts against morality, as regulated in the provisions of Article 289 of the Criminal Code and Article 4 paragraph (2b) of Law Number 12 of 2022 concerning Crimes of Sexual Violence. The aim of the research is to analyze and discuss the factors that cause criminal acts of child molestation accompanied by violence as well as analyze and discuss countermeasures in dealing with criminal acts of child molestation accompanied by violence by the Ambon Island Police and P.P. Leases. The research method used is empirical juridical research, the data sources are primary data and secondary data. Data collection techniques through observation, interviews, literature, documentation and qualitative descriptive analysis. The factors that cause the crime of child molestation accompanied by violence are environmental factors, consisting of (residential environment, family environment, and social relations), technological development factors such as the use of social media Facebook, the victim being easy to meet, the low level factor. Economy and unemployment and factor education. Mitigation efforts in dealing with criminal acts of child molestation accompanied by violence by the Ambon Island Police and P.P Lease, include preventive action, preemptive action and repressive action, including conducting counseling or socialization by the Binmas Unit in the form of legal education and appeals carried out in several places. . Policewomen activities through Goes To School by PPA Unit Officers, and PPA Policewomen in collaboration with victim assistants, namely P2TP2A (Integrated Service Center for Empowerment of Women and Children) Ambon City in the form of outreach. Investigators are carrying out law enforcement efforts against perpetrators of criminal acts of child molestation accompanied by violence.